Edwin's Representations of Feminism in the Thorny Fog Film: A Semiotic Study of John Fiske - Ahmad Ilzamul Hikam; Mohammad Husen; Mohammad Saied (Molang: Journal Islamic Education, 2026)
The film Mist of Thorns tells the story of a man named Sanja who becomes a detective investigating a serial murder and human trafficking case in Kalimantan. Sanja is not only playing the role of investigating the case, but also trying to voice the voices of women who are blocked, and fighting against the patriarchal social system in the police force. Therefore, the researcher is interested in analyzing the feminism in the film Mist of Thorns using John Fiske's semiotics. The purpose of this study is to describe the feminism in the film Mist of Thorns, using John Fiske's semiotic study which has three levels, the level of reality, the level of representation, and the level of ideology. The benefits of this study can be used as a reference for further research and can increase insight into literature, especially feminism. The data collection technique uses the technique of observing, recording and documentation. The data analysis technique uses data reduction and presentation. The results of this study found that there are three feminisms in the film Mist of Thorns, namely, three liberal feminisms, one radical feminism, and one transformative feminism.